Pengaruh Fasilitas dan Daya Tarik Wisata Terhadap Kepuasan Pengunjung Pada Objek Wisata Pemandian Alam Karomah - Ainul Hayat Sirait; Edi Winata (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this study was to determine whether there is an effect of facilities and tourist attractions on visitor satisfaction on visitor satisfaction at the Karomah Natural Baths. The sample of this study was 86 people, sampling using incidental sampling, namely determining the sample who happened to meet. Data analysis used Multiple Regression test, while data processing used SPSS. The results showed that partially the facility variable has a positive and significant effect on visitor satisfaction, and partially the attractiveness variable has a positive and significant effect on visitor satisfaction, while simultaneously facilities and attractiveness have a positive and significant effect on visitor satisfaction.